2012
DOI: 10.1177/147470491201000303
|View full text |Cite
|
Sign up to set email alerts
|

What Have You Done for Me Lately? Friendship-Selection in the Shadow of the Dark Triad Traits

Abstract: The current studies examined how the Dark Triad personality traits (i.e., Machiavellianism, narcissism, and psychopathy) facilitate the strategic structuring of an individual's social environment in terms of same- and opposite-sex friends. In one study using normative questions (N = 267) and another using a budget-allocation task (N = 114), we found that the Dark Triad traits were associated with choosing friends for strategic purposes and to create a volatile environment. Narcissistic individuals reported rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 71 publications
2
82
0
Order By: Relevance
“…Machiavellianism was associated with lower scores on all of the six friendshipfunctions subscales. Although same-sex friendships are often labelled as being highly important to women and provide a variety of functions and resources (Jonason & Schmitt, 2012;Silverman & Choi, 2005;Vigil, 2007), women with higher levels of Machiavellianism may view such functions as unnecessary. It is not surprising that women with higher levels of Machiavellianism have reported that their friend provides them with less companionship, help, intimacy, reliable alliance, self-validation, and emotional security.…”
Section: Study 1 Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Machiavellianism was associated with lower scores on all of the six friendshipfunctions subscales. Although same-sex friendships are often labelled as being highly important to women and provide a variety of functions and resources (Jonason & Schmitt, 2012;Silverman & Choi, 2005;Vigil, 2007), women with higher levels of Machiavellianism may view such functions as unnecessary. It is not surprising that women with higher levels of Machiavellianism have reported that their friend provides them with less companionship, help, intimacy, reliable alliance, self-validation, and emotional security.…”
Section: Study 1 Discussionmentioning
confidence: 99%
“…Research also demonstrates that adults with high Machiavellianism levels select opposite-sex friends who are kind (Jonason &Schmitt, 2012). This may indicate a preference for friends that can be easily exploited.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, it may be that the Machiavellian reports concern for others because they know that in order to use people in the future, they need to maintain a certain level of friendship. Jonason and Schmitt (2012) found that individuals who scored high on the Dark Triad tended to form friendships for strategic purposes. This finding lends some support to the notion that if the Machiavellian were to completely disregard others' feelings, it is unlikely these individuals will remain present long enough to be useful to them.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few studies have examined friendship motivation and narcissism, but many suggest that narcissists likely lack interest in developing high-quality friendships. Jonason and Schmitt (2012) found that narcissism was positively related to preferring agentic, competence-related qualities in friends, but unrelated to favoring communal, relationship-oriented qualities (e.g., kindness, trustworthiness), suggesting that narcissists have a more instrumental view of friendship. These findings are consistent with the agency model of narcissism (Campbell & Green, 2008), which maintains that narcissism is characterized by a focus on agentic over communal concerns and interpersonal self-regulation strategies focused on self-enhancement.…”
Section: Introductionmentioning
confidence: 94%